Does educational intervention improve doctors’ knowledge and perceptions of generic medicines and their generic prescribing rate? A study from Malaysia - Hassali, Mohamed Azmi (SAGE Open Med, 2014)
OBJECTIVES: To investigate the impact of an educational intervention on doctors’ knowledge and perceptions towards generic medicines and their generic (international non-proprietary name) prescribing practice. METHODS: This is a single-cohort pre-/post-intervention pilot study. The study was conducted in a tertiary care hospital in Perak, Malaysia. All doctors from the internal medicine department were invited to participate in the educational intervention. The intervention consisted of an interactive lecture, an educational booklet and a drug list. Doctors’ knowledge and perceptions were assessed by using a validated questionnaire, while the international non-proprietary name prescribing practice was assessed by screening the prescription before and after the intervention. RESULTS: The intervention was effective in improving doctors’ knowledge towards bioequivalence, similarity of generic medicines and safety standards required for generic medicine registration (p = 0.034, p = 0.034 and p = 0.022, respectively). In terms of perceptions towards generic medicines, no significant changes were noted (p > 0.05). Similarly, no impact on international non-proprietary name prescribing practice was observed after the intervention (p > 0.05). CONCLUSION: Doctors had inadequate knowledge and misconceptions about generic medicines before the intervention. Moreover, international non-proprietary name prescribing was not a common practice. However, the educational intervention was only effective in improving doctors’ knowledge of generic medicines.